Types and proportions of vannamei shrimp (Litopeneus vannamei) commodity marketing channels at Kendari Ocean Fisheries Port - Yani, Kitri Warda; Siang, Roslindah Daeng; Nur, Andi Irwan (Universitas Halu Oleo, 2024)
This study aimed to determine the type and purpose of marketing channels, to determine the proportion of vannamei shrimp marketing channels at the Ocean Fisheries Port, Kendari. Research data was obtained through observation, direct interviews, documentation and literature study. The sampling method used was purposive sampling method. The data analysis used was descriptive using a percentage approach to marketing proportion analysis. The results obtained were the type of marketing channel, which is indirect, because it was through the intermediary of branch companies and the head office of PT. Yanagi Histalaraya, while the market objectives were the domestic and export markets. The proportion of distribution volume was greater in the domestic market than in the export market. The proportion of domestic market marketing types was highest in 2016 while the lowest was in 2020 with no distribution at all. The proportion in the export market type was highest in 2017 and lowest one was in 2018 to 2020 with no distribution at all